2021
DOI: 10.1136/bmjopen-2020-046187
|View full text |Cite
|
Sign up to set email alerts
|

What are the consequences of caring for older people and what interventions are effective for supporting unpaid carers? A rapid review of systematic reviews

Abstract: ObjectivesTo identify and map evidence about the consequences of unpaid caring for all carers of older people, and effective interventions to support this carer population.DesignA rapid review of systematic reviews, focused on the consequences for carers of unpaid caring for older people, and interventions to support this heterogeneous group of carers. Reviews of carers of all ages were eligible, with any outcome measures relating to carers’ health, and social and financial well-being. Searches were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…As the treatment took place in the home environment of both patients and families, it was quite natural that family members became involved either as observers or active partners in solving practical tasks related to the treatment. Several studies on chronic diseases describe how long-term caregiving can be a burden for the caregiver and how hospital admission can be a ‘break’ for the caregivers 14. Our study showed that from a patient’s perspective, family involvement was perceived as something positive and not a burden.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As the treatment took place in the home environment of both patients and families, it was quite natural that family members became involved either as observers or active partners in solving practical tasks related to the treatment. Several studies on chronic diseases describe how long-term caregiving can be a burden for the caregiver and how hospital admission can be a ‘break’ for the caregivers 14. Our study showed that from a patient’s perspective, family involvement was perceived as something positive and not a burden.…”
Section: Discussionmentioning
confidence: 55%
“…Several studies on chronic diseases describe how long-term caregiving can be a burden for the caregiver and how hospital admission can be a ‘break’ for the caregivers. 14 Our study showed that from a patient’s perspective, family involvement was perceived as something positive and not a burden. However, little is known about the caregivers’ perspective on short-term and temporary caregiving during home treatment, which should be explored in future research.…”
Section: Discussionmentioning
confidence: 62%
“…Although we did not assess these aboriginal FCGs’ health and wellbeing, worldwide, FCGs are at increased risk of deteriorating health [ 42 , 43 ] and financial insecurity [ 44 ] which makes the FCG role itself a public health issue and social determinant of health [ 42 , 45 ]. Both Public Health England [ 42 ] and the American National Caregiving Alliance [ 45 ] point to a greater proportion of FCGs than noncarers with chronic conditions and had difficulty taking care of their own health. Framing family caregiving from the public health perspective positions issues related FCGs’ work and role as a lifecourse population health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, research exploring the social impact of caregiving in other injury types is lacking (e.g., for orthopaedic injuries). The challenges and demands of caring for older people are well documented; however, a recent review of systematic reviews by Spiers et al [ 14 ] stated that current evidence fails to quantify the impact of caregiving on wellbeing. Authors suggested the need for a comprehensive review to explore the impact of caring for older people on outcomes in terms of social and financial well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Research typically investigates shorter term impacts following injury, despite evidence of financial burden continuing over many years [ 18 ]. It is well known that unpaid caring for older people can lead to a loss of employment or reduction in working hours [ 14 ], with many carers having to manage employment alongside caring responsibilities. However, there is limited evidence to describe the impact of this dual role on financial and social wellbeing not only in the widely studied older person carer population [ 14 ], but also in the traumatic injury carer population.…”
Section: Introductionmentioning
confidence: 99%